Evaluasi Implementasi Program Pengungkapan Sukarela (PPS) pada KPP Pratama Jakarta Tambora - Putri, Indah Yuliana; Rosid, Arifin (Owner : Riset dan Jurnal Akuntansi, 2024)
Tax revenue is still the most important source of income in Indonesia, it can be seen that taxes contribute 80% of the total state revenue in 2023. One policy that is widely used by the state to raise state revenue is the tax amnesty policy. Indonesia has implemented several tax amnesty policies, the Voluntary Disclosure Program is the latest tax amnesty policy implemented in Indonesia. This study aims to evaluate the implementation of the Voluntary Disclosure Program (VDP) for Individual Taxpayers at KPP Pratama Jakarta Tambora. The results of this evaluation are expected to be input for the Directorate General of Taxes in making future tax amnesty policies. This research uses descriptive qualitative method based on the OECD evaluation criteria framework to evaluate PPS. The data used in this research is primary data obtained from interviews with the Head of Office, three Account Representatives, and a Tax Extension Supervisor. In addition, this study also uses secondary data from the Directorate General of Taxes (DGT). The result of this research is that PPS succeeds in optimizing tax revenue, broadening the tax base, and creating compliance in the short term, but PPS does not succeed in creating taxpayer voluntary compliance in the long term. It is hoped that in the future the government will not implement tax amnesty programs too often and tax amnesty policies should be followed by law enforcement in order to create sustainable compliance.